(The Effect of Chitosan Addition and Sedimentation Time on Wastewater Treatment of Leathers Tanning Industries) - Eddy Sapto Hartanto; Syarif Bastaman; Padmono Citroreksoko (Warta Industri Hasil Pertanian, 1993)
The use of chitosan as a flocculation in the treatment of liquid waste of leather tanning industry has been studied.Chitosan was used together with commercial polymers PA 322 and PN 161. It was found tahat the addition of 1% solution of chitosan and polymers significantly affected the decrease of turbidity,suspended solid,cod,and chrom content.The use of 1% sulition along with 90 minutes settling gave the best result i.e. lessened the turbidity 98.8%,suspended soild 97.9%,COD 84%,and chorm content 100%.